2018
DOI: 10.1161/atvbaha.117.310517
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Monocytic Cells in Regressing Atherosclerotic Plaques by Intravital 2-Photon and Positron Emission Tomography–Based Imaging—Brief Report

Abstract: Cervical transplantation of atherosclerotic mouse aortic arches represents a novel experimental tool to investigate cellular mechanisms that contribute to the remodeling of atherosclerotic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Intravital imaging of atherosclerotic plaques is challenging, not least because of the need to confront motion associated with breathing and heart rhythm in the arterial tree. However, using different approaches, these hurdles are being overcome in different groups, largely either with the use of software that collects images in rhythm with the heart beat 7 or with physical stabilization of arterial tissue to reduce motion 6, 11 . We developed a preparation capable of direct imaging of established plaque in the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravital imaging of atherosclerotic plaques is challenging, not least because of the need to confront motion associated with breathing and heart rhythm in the arterial tree. However, using different approaches, these hurdles are being overcome in different groups, largely either with the use of software that collects images in rhythm with the heart beat 7 or with physical stabilization of arterial tissue to reduce motion 6, 11 . We developed a preparation capable of direct imaging of established plaque in the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a preparation capable of direct imaging of established plaque in the carotid artery. To our knowledge, our preparation is the first to image high fat-diet induced established plaques native to the animal being evaluated, as compared with injury-induced plaques 6 , transplanted vessels 11 , or monocyte interactions with the vessel wall prior to plaque progression 8 . Having developed a stable and high resolution imaging approach, we found that macrophages piled in clusters within the plaque were highly sessile, displaying minimal net displacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET tracers targeted at C-C chemokine receptor type 5 (CCR5), type 2 (CCR2), and other immune cell chemokine surface receptors have been evaluated in animal models of vascular injury and atherosclerosis [29][30][31][32]. In one study, the feasibility of imaging 8 chemokine receptors simultaneously was tested using targeted nanoparticles [33].…”
mentioning
confidence: 99%
“…In this model, a murine heart is transplanted into the neck of a recipient and the graft is stabilized, which enables intravital imaging for several hours. Appreciating the work done by Chevre and colleagues [7], where intravital two-photon imaging was applied to carotid artery atherosclerotic lesions, we developed a method of cervical aortic arch transplantation [8]. By transplanting plaque-bearing aortic arches from apoE-deficient mice into the neck of CX 3 CR1 GFP-reporter mice, we were able to stabilize the grafts and visualize the recruitment of CX 3 CR1 + monocytes into atherosclerotic plaques in real time, where they display only little motility and progressively decrease in number as the lesions regress.…”
mentioning
confidence: 99%